2008
DOI: 10.1080/03079450701802255
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of budgerigars (Melopsittacus undulatus) with fiveMycobacteriumspecies

Abstract: International audienceThe aim of the present study was to determine the susceptibility of budgerigars (Melopsittacus undulatus) to infections with different Mycobacterium species. For inoculations the following M. species were used: M. avium subsp. avium, M. bovis subsp. bovis, M. tuberculosis subsp. tuberculosis, M. intracellulare and M. fortuitum subsp. fortuitum. The bacterial suspension was administrated intramuscularly and all the birds were monitored for 70 days starting from the day of inoculation. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The long incubation period of 2.5 years in the present case is in accordance with other cases known from literature, in which incubation periods were estimated between 0.5 and 4 years, respectively (Washko et al, 1998;Steinmetz et al, 2006;Peters et al, 2007). In a recently published experimental infection study, a long incubation period for M. tuberculosis infection could also be confirmed in budgerigars (Ledwon et al, 2008). Contrary to the clinical signs described above for the blue-fronted amazon and the green-winged macaw, facial lesions were absent in the African Grey parrot.…”
Section: Discussionsupporting
confidence: 93%
“…The long incubation period of 2.5 years in the present case is in accordance with other cases known from literature, in which incubation periods were estimated between 0.5 and 4 years, respectively (Washko et al, 1998;Steinmetz et al, 2006;Peters et al, 2007). In a recently published experimental infection study, a long incubation period for M. tuberculosis infection could also be confirmed in budgerigars (Ledwon et al, 2008). Contrary to the clinical signs described above for the blue-fronted amazon and the green-winged macaw, facial lesions were absent in the African Grey parrot.…”
Section: Discussionsupporting
confidence: 93%
“…avium , which caused no clinical or pathological changes typical of mycobacteriosis [12]. In the present study when we used the same amount of bacteria in the same environmental conditions, advanced mycobacteriosis was endangered.…”
Section: Discussionmentioning
confidence: 86%
“…Only a few samples were positive despite the advanced pathological changes in the internal organs. Our previous study involving other species of mycobacteria cultures of faeces proved also unsatisfactory in terms of the anticipated number of positive samples [12]. Thus, cloacal and crop swabs do not constitute valuable material for diagnostics of Mycobacterium avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subclinical infections are also common, making detection and containment of the disease difficult [18]. These subclinical infections are difficult to detect from blood samples, as has previously been shown in clinically healthy but BFDV-positive budgerigars, where more often than not, the blood samples tested negative [19]. Hess et al [20] suggested that there is a correlation between clinical signs and viraemia as assayed using PCR during a longitudinal study of captive budgerigars; however, the correlation between Electronic supplementary material The online version of this article (doi:10.1007/s00705-014-2225-x) contains supplementary material, which is available to authorized users.…”
mentioning
confidence: 93%